'The law is not for the poor': Land, law and eviction in Luanda. Issue 3 (1st August 2016) - Waldorff, Pétur
Abstract : This article investigates how an existing two‐tiered land tenure system creates a hybrid space that blurs, and essentially questions and problematizes the boundaries of the formal/informal divide as presented within Angolan political and legal discourses. It showcases how urban formality and informality exist alongside each other in Luanda and how people take recourse to both formal and informal channels in attempts to secure housing, land tenure and livelihoods in the city. Through case studies, the article describes how small‐scale farmers in Luanda's northern municipality of Cacuaco lost their lands to urban development in 2009–10 and the ensuing circumstances in which formal rights and informal land tenure became intermeshed and ambiguous. As the case studies illustrate, a gap exists between the legal code and practice on the ground. This gap is represented in how Angola's postconflict land strategy, with its forced evictions and demolitions of houses and neighbourhoods, often with little or no compensation, is at odds with the Angolan Land Law, which states that land may only be expropriated by the state or local authorities for specific public use and must be justly compensated.